Hubungan Digitalisasi Arsip terhadap Efektivitas Kerja Pegawai di BPK Perwakilan Provinsi Jatim - Andia Rahma (Jurnal Ilmiah Dan Karya Mahasiswa, 2026)
Digital transformation in the public sector has encouraged organizations and institutions to implement archive digitalization as an effort to improve information management, efficiency, and work effectiveness. This study aimed to examine the relationship between archive digitalization and employee work effectiveness at the Audit Board of the Republic of Indonesia (BPK) Office for East Java Province. This research employed a quantitative approach with a correlational design. The sample consisted of 24 employees selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using the Pearson Product Moment correlation test with the assistance of SPSS software at a significance level of 0.05. The results showed a Pearson correlation coefficient of r = 0.911 with a significance value of p = 0.000. These findings indicate a very strong and statistically significant positive relationship between archive digitalization and employee work effectiveness. Archive digitalization plays an important role in supporting faster information access, accurate document management, and improved employee productivity within public sector organizations.